Charging of car battery in electric vehicle by using wind energy. (2021) - Zahir Hussain, M.; Anbalagan, R.; Jayabalakrishnan, D.; Naga Muruga, D.B.; Prabhahar, M.; Bhaskar, K.; Sendilvelan, S.
Abstract: The battery is a storage unit which consists of many cells, is used to produce power by undergoing some chemical process so that chemical energy is produced, and converted into electric energy, that is used as a source of power in vehicles. In conventional Engine vehicles, the batteries are used only to power the components like starter motor, horn and so on. Thus, the rate of battery discharging is slow. But today, the world is moving towards the production and use of Electric Vehicles (EV's), in which batteries are the primary source of power. This demands for batteries with larger capacity for EV's. Even though high-power capacity batteries are used, they tend to discharge at a much faster rate and demands charging every day. To charge these batteries, there must be very high-power input and also the charging time is more (3 to 4 h for full charge). Due to this disadvantage, people do not prefer EV's. Thus, the concept is to introduce a system which can charge the battery when the vehicle is in motion i.e., without stopping the vehicle for charging. To enable this, the most renewable source of energy is being utilized which is Wind Energy. To harness this wind energy, the Vertical Axis Wind Turbine (VAWT) is used. The VAWT will be placed inside the front grille of the vehicle where there will be air flow, which will propel the turbine, and thus power is generated. This system is capable of reducing the time and money spent for battery charging in the EV's.